Occupational Safety Risk Assessment at XX Hospital Using The Safety Risk Assessment Method - Rachmananda, Al Rifky; Widodo, Silvi Rushanti (School of Industrial and System Engineering, Telkom University, 2024)
Occupational safety in hospitals is a crucial aspect directly related to service quality and employee well- being. This study aims to identify hazard sources, assess risk levels, and formulate appropriate control measures at XX Hospital using the Safety Risk Assessment (SRA) method. A descriptive approach was applied through observation, interviews, and documentation, involving both medical and non-medical personnel selected using purposive sampling. The analysis revealed that most respondents had low to moderate likelihood scores, with risk severity ranging from mild to moderate. The most frequent risks identified included infection from patient body fluids, injuries while transferring patients, eye strain from prolonged computer use, mental fatigue due to workload, and emotional stress from public interaction. Although most risks were categorized as low, several required immediate control, particularly physical activities such as patient handling. Recommended strategies include engineering controls, administrative measures, and consistent use of personal protective equipment (PPE). This study emphasizes the importance of implementing comprehensive risk assessments in hospitals to strengthen occupational health and safety (OHS) management systems. The findings are expected to serve as a basis for developing more strategic, applicable, and preventive safety policies to ensure a safe and productive hospital work environment.